The impact of duration on effectiveness of exercise, the implication for periodization of training and goal setting for individuals who are overfat, a meta-analysis - Clark, JE (Biology of Sport, 2016)
Given the assumption that all methods of exercise, e.g., endurance (ET), resistance (RT), or combination of both (E+R), can induce a beneficial effect size (ES) for changes in body composition and health status of individuals who are overfat. Thus the aim and purpose of this study is to evaluate the current body of knowledge to address the question as to the impact that the duration of exercise has on its relative effectiveness for inducing health and body compositional changes in individuals who are overfat to assist with developing periodized exercise protocols and establishing short and long term goals. A tiered meta-analysis of 92-studies and 200-exercise groupings were used for establishing pooled ES within and between groupings based on the increments of 4-week of duration and study designs of ≤8, 9-16, 17-23, 24-36, and ≥36 weeks. Analysis based on random-effect of response indicates a continuum of effectiveness within and between ET, RT and E+R based on duration. Where beneficial effectiveness is not indicated for any measures until after 8-weeks of continuous training with progressive effectiveness being noted in changes to cardiorespiratory fitness, inflammatory cytokines, and alteration of metabolic status from 12-weeks through 32-weeks of continuous training. Results indicate a greater ES for RT and E+R versus ET early in intervention that equalizes with longer durations. Supporting the use of RT and E+R within a periodized program. And secondarily, goals should be established first on performance gains and second body composition or health status modifications for the individual who is overfat.